2021
DOI: 10.1038/s42003-020-01552-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrated molecular characterisation of the MAPK pathways in human cancers reveals pharmacologically vulnerable mutations and gene dependencies

Abstract: The mitogen-activated protein kinase (MAPK) pathways are crucial regulators of the cellular processes that fuel the malignant transformation of normal cells. The molecular aberrations which lead to cancer involve mutations in, and transcription variations of, various MAPK pathway genes. Here, we examine the genome sequences of 40,848 patient-derived tumours representing 101 distinct human cancers to identify cancer-associated mutations in MAPK signalling pathway genes. We show that patients with tumours that h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 85 publications
(109 reference statements)
3
28
0
Order By: Relevance
“…The MAPK cascade is a highly conserved signalling pathway with oncogenic roles 113,114 . Activating mutations in genes encoding MAPK pathway components (such as KRAS, HRAS, BRAF and MEK1/2) are very rare in TNBC; however, the amplification of these genes and non-canonical mechanisms of MAPK pathway activation, including the overexpression of growth factor receptors (such as EGFR, FGFR1 and IGF1R) or loss of negative regulators (including NF1 or DUSP4), have been described and might occur in ~3% of TNBCs, although their incidence is hard to estimate 32,104 .…”
Section: Mapk Pathway Inhibitorsmentioning
confidence: 99%
“…The MAPK cascade is a highly conserved signalling pathway with oncogenic roles 113,114 . Activating mutations in genes encoding MAPK pathway components (such as KRAS, HRAS, BRAF and MEK1/2) are very rare in TNBC; however, the amplification of these genes and non-canonical mechanisms of MAPK pathway activation, including the overexpression of growth factor receptors (such as EGFR, FGFR1 and IGF1R) or loss of negative regulators (including NF1 or DUSP4), have been described and might occur in ~3% of TNBCs, although their incidence is hard to estimate 32,104 .…”
Section: Mapk Pathway Inhibitorsmentioning
confidence: 99%
“…The latter is a promising approach that is likely to improve treatment outcomes, as the strategy would not depend on the biological importance of the targeted CSRs within downstream signalling pathways: irrespective of its biological function, any CSR that is expressed in tumour cells but not in healthy cells would be a viable target. This approach to anticancer therapy promises fewer disease remissions and better efficacy than current treatments as non-specifically cytotoxic compounds would not, like current chemotherapeutics, only kill tumour cells with a specific molecular phenotype [34][35][36][37][38]. For as long as the cells in the tumour express the targeted CSR, the non-specific toxin(s) that is(are) delivered to these cells will kill all the cells in their proximity, including those that do not express the CSR.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple omics data are often generated to examine various biological aspects of drug-resistant cancer cells (Figure 1). Target genotypes and phenotypes examined using omics data (Table 1) include: cancer-associated mutations (Niehr et al, 2018;Marczyk et al, 2020;Sinkala et al, 2021); changes in the expression level of specific genes (Niehr et al, 2018;Nava et al, 2019;Kagohara et al, 2020;Marczyk et al, 2020;Poojan et al, 2020;Sinkala et al, 2021); changes in chromosome structure (Kagohara et al, 2020;Marczyk et al, 2020;Aissa et al, 2021); epigenetic alterations (e.g., methylation or acetylation states of histone • Methylome (reduced representation bisulfite sequencing)…”
Section: Multi-omics Analysesmentioning
confidence: 99%
“…• ceRNA network for correlation between lncRNA and mRNA levels using RNA-seq data proteins) (Nava et al, 2019;Kagohara et al, 2020;Marczyk et al, 2020;Poojan et al, 2020;Sinkala et al, 2021); and the presence of heterogeneity of a cell population (Niehr et al, 2018), often increasingly examined at a single-cell resolution (Kagohara et al, 2020;Aissa et al, 2021). In a recent study for cell line heterogeneity, for example, application of single-cell DNA and RNA sequencing (RNA-seq) to 20 triple-negative breast cancer (TNBC) patients revealed that rare pre-existing clones having genotypes associated with chemoresistance were adaptively selected in response to neoadjuvant chemotherapy, which subsequently led to acquired transcriptional reprogramming (Kim et al, 2018).…”
Section: Multi-omics Analysesmentioning
confidence: 99%